The multifaceted roles of E3 ubiquitin ligases in osteoarthritis - Jin, Zheng; Zhu, Zhenhua; Chen, Jun; Jing, Xiaopeng; Tan, Jie; Zeng, Ji (Frontiers in Cell and Developmental Biology, 2025)
Osteoarthritis (OA) is the most widespread joint disorder worldwide. It is a major cause of lower limb mobility issues in the elderly. With the ongoing aging of the global population and the increasing prevalence of obesity, the disease burden associated with OA is expected to rise significantly. E3 ubiquitin ligases (E3s) play a crucial role in protein ubiquitination. They identify specific substrates and attach ubiquitin molecules to substrates, thus modulating protein stability, function, and cellular localization. E3s can be classified into three main types: RING-, HECT-, and RBR-type E3s. Growing evidence indicates that E3s affect OA by regulating the degradation of extracellular matrix (ECM) proteins and inflammatory responses. This review highlights the functions and underlying mechanisms of E3s in OA, aiming to provide new therapeutic insights for the treatment of OA.